Sistem Pelaporan Kerusakan Jalan dan Saluran Air Berbasis Website dengan Metode SAW - Ahmad Habib; Irfan Dwi Arfianto (METIK Jurnal, 2026)
Road and drainage infrastructure damage significantly affects public mobility and service quality. However,  the reporting process in many regions in Indonesia is still performed manually through messaging applications, making the information incomplete, unverified, and difficult to follow up. This study develops a web-basedinfrastructure damage reporting system integrated with GPS and the Simple Additive Weighting (SAW) method to support decision-making in prioritizing repair actions. The system allows the public to submit reports by uploading photos, descriptions, and coordinates automatically captured from the device. Administrators can verify incoming reports and assign values based on four criteria: damage level, location strategic value, road usage intensity, and proximity to public facilities. The SAW method is applied to calculate the priority ranking of handling each report. The research method uses the Waterfall model consisting of requirements analysis, system design using ObjectOriented Design (OOD) and UML, implementation using Laravel, and testing using Black-Box and usability testing. The results show that the system operates well, GPS data is captured accurately, the SAW calculation generates correct priority scores, and the system is easy for users to operate. This system is expected to improve the accuracy, speed, and transparency of reporting and become a digital solution for regional agencies to support infrastructure handling based on data-driven decisions.